answersLogoWhite

0


Best Answer

8y - = 15 + 2y

User Avatar

Wiki User

โˆ™ 2008-11-18 05:45:46
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.74
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
1027 Reviews

Add your answer:

Earn +20 pts
Q: How do you do this problem 8y - 3 15 2y?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What is 8y minus 3 equals 15 plus 2y?

y equals 3


How do you do the sum 8y-2 equals 3-2y?

If: 8y-2 = 3-2y Then: 8y+2y = 3+2 So: 10y = 5 Therefore: y = 5/10 or as a 1/2 in its simplest form


What is 8y-7 equals 23-2y?

let's solve this problem:-the first step; (find the 'y')8y-7 = 23 -2y8y+2y = 23+710y = 30y = 30:10y = 3-the second step; (change the 'y' with '3')8(3) -7 = 23 -2(3)24 -7 = 23 -617 = 17well, The conclusion and the answer is;8y -7 = 23 - 2y --> is True Equal ;)


What is the factorization of 8y 12?

4(2y + 3)


How do you factor 8y-12?

4(2y-3)


How do you factor 8y cubed plus 27?

Not sure which you mean, take your pick: (8y)3+27=(8y+3)((8y)2-3*(8y)+9)=(8y+3)(64y2-24y+9); or 8y3+27=(2y+3)(4y2-6y+9)


How do you factor 2y cubed minus 8y squared minus 42y?

2y(y + 3)(y - 7)


What is x-2y equals 0 in 4x-3y equals 15?

eq. 1 is x-2y=0 which means x=2y eq. 2 is 4x-3y=15 subst. x=2y in eq. 2 4(2y)-3y=15 8y-3y=15 5y=15 y=3 subst. y=3 in eq. 1 we get x=2(3) x=6 Ans: x=6 and y=3 is the required solution. Thank you.


How do you factor 8y -12?

20


What is the slope of the equation 2y equals 6x minus 8?

2y = 6x - 8y = 3x - 4========m(slope) = 3=========


Solving by subsitution x - 2y equals 0 4x - 3y equals 15?

x - 2y = 04x - 3y = 15From the first equation, x = 2y.SUBSTITUTING this value of x in the second equation,4*(2y) - 3y = 15 ie 8y - 3y = 15 or 5y = 15 so that y = 3and then, x = 2y gives x = 2*3 = 6Answer: x = 6, y = 3


How would I simplify 8y plus 2y plus 3y?

It is like saying, "How much is 8 yams plus 2 yams plus 3 yams?" Add the numbers: 8+2+3 = 13. The answer is the number of yams. 8y+2y+3y = (8+2+3)y = 13y.

People also asked